The Reality Of The Process Of Sports Selection For School Teams In Handball From The Point Of View Of Physical Education Teachers - Rebbouh, Abdenacer; Kenioua, Mouloud; Zeroual, Mohammed (Journal of Sport Science Technology and Physical Activities, 2023)
The Object of the study aims to identify the reality of the sports selection process for school teams in handball from the point of view of physical education teachers, for this purpose, we used the descriptive method on a sample composed of 50 physical education teachers. Chosen as randomly, and for data collection, we used a questionnaire After collecting the results and having treated them statistically, we conclude that the process of sports selection for the school teams is subject to the foundations and scientific standards by the physical education teacher, in addition to that there are no statistically significant differences between the teachers of physical education in the selection process for the school teams in handball due to the professional experience. On this basis, the study recommended that it is necessary to improve working conditions for physical education teachers by providing all the capabilities and means required by the selection process for school teams.